The relationship between problematic technology use and acquisition of social values: digital world-real values - Avci, Alperen; Sapsaglam, Ozkan (Routledge Journals, Taylor & Francis Ltd, 2025)
Problematic technology use is defined as a condition in which individuals experience adverse effects in their physical, psychological and social lives due to excessive and uncontrolled use of technological devices. This study aimed to examine the relationship between problematic technology use and the acquisition of social values in preschool children through an explanatory sequential design, integrating a quantitative phase that included 124 children aged 3-5 years and their mothers, while the qualitative phase involved 18 children, nine identified as problematic technology users and their teachers. Mothers evaluated their children's levels of technology use, while data on children's acquisition of social values were directly collected by the researcher through individual assessments. Teachers also observed children's social behaviours in the classroom. Data were gathered using the Problematic Technology Use Scale for Young Children and the Social Value Acquisition Scale. Qualitative data were obtained through children's drawings and teacher focus group interviews. The findings revealed that increased technology use was associated with decreases in social values such as love, respect, responsibility, cooperations and kindness. The study highlights the developmental risks of excessive technology use in early childhood.
Keywords: Early Childhood; Technology; Problematic Technology Use; Values; Social Values